2015
DOI: 10.3109/10715762.2015.1016018
|View full text |Cite
|
Sign up to set email alerts
|

Naringin inhibits gamma radiation-induced oxidative DNA damage and inflammation, by modulating p53 and NF-κB signaling pathways in murine splenocytes

Abstract: The adverse effects of ionizing radiation occur due to the generation of reactive oxygen species (ROS). The aim of this study was to identify the protective effects of naringin (NG), a citrus flavonoid, on ionizing radiation (IR)-induced differential stress response, with an exploration of the mechanisms involved in this process. Isolated murine splenocytes were incubated in the presence and in the absence of different concentrations of NG (50 and 100 μM) for 1 h prior to 6 Gy γ-irradiation, and the molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 45 publications
4
46
0
Order By: Relevance
“…The phosphorylation and translocation of NF-κB were also increased after exposure to gamma radiation, which were blocked upon the treatment of UA. Our observations could be supported by a recent study from Manna et al (2015), who showed that naringin inhibited gamma radiation-caused inflammation and oxidative DNA damage by controlling p53 and NF-κB signaling pathways in murine splenocytes (Manna et al, 2015). In another report, Lee et al (2014) showed that UV light exposure produced a loss of proliferation and an activation of NF-κB in the skin melanoma cells, while pre-treatment with UA significantly reduced the amount of phosphorylated NF-κB at 24 h post-exposure (Lee et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The phosphorylation and translocation of NF-κB were also increased after exposure to gamma radiation, which were blocked upon the treatment of UA. Our observations could be supported by a recent study from Manna et al (2015), who showed that naringin inhibited gamma radiation-caused inflammation and oxidative DNA damage by controlling p53 and NF-κB signaling pathways in murine splenocytes (Manna et al, 2015). In another report, Lee et al (2014) showed that UV light exposure produced a loss of proliferation and an activation of NF-κB in the skin melanoma cells, while pre-treatment with UA significantly reduced the amount of phosphorylated NF-κB at 24 h post-exposure (Lee et al, 2014).…”
Section: Discussionsupporting
confidence: 83%
“…The modulation of NF-κB contributes to the survival of the irradiated cells (Manna et al, 2015). Our results demonstrated that exposure to the gamma radiation dose- and time-dependently increased NF-κB DNA binding activities in HaCaT cells, and UA treatment significantly suppressed this increase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also found that naringin is protective against inflammatory reaction [6]. Recently, it was reported that naringin protects against joint destruction in inflammatory arthritis models [7].…”
Section: Introductionmentioning
confidence: 97%
“…The importance of NF-κB in mediating irradiation-induced inflammatory responses has been recently shown by Manna et al, who, by selectively inhibiting NF-κB activity, could successfully reverse IR-induced stress response and inflammation development by downregulating the expression of CRP (C reactive protein), MCP-1 (monocyte chemotactic protein) and iNOS2 (inducible nitric oxide synthase 2). 147 Radiation-induced cytokine gene upregulation is often a biphasic process. Several inflammation-related cytokine genes are characteristically immediate early response genes that are activated within minutes to hours after irradiation.…”
Section: 136mentioning
confidence: 99%